Wartime Housing and Architectural Change, 1942-1992 - Adams, Annmarie; Sijpkes, Pieter (Ethnologies, 1995)
This paper comprises the intermediate results of a study of architectural changes made to wartime houses over a fifty-year period in Ville St-Laurent, Quebec, Canada. Our study shows several basic patterns in the ways people changed their spaces over time. In-depth interviews with longtime occupants and a comprehensive photographie survey of the area show that it was their wartime work experience which encouraged most householders to undertake renovations themselves; that the employment of professionals for extremely difficult jobs followed a kind of “copy-cat” phenomenon which can be mapped throughout the neighbourhood; and that many women supervised the alterations made to their houses.